Business to business marketing management : a global perspective - Zimmerman, Alan S., 1942-; Blythe, Jim, 1951- (Routledge, Taylor & Francis Group, 2022)
"Business to Business (B2B) markets are considerably more challenging than consumer markets and demand a more specific skillset from marketers. B2B buyers, often dealing with highly complex products, have specialist product knowledge and are far more knowledgeable and demanding than the average consumer. This textbook takes a uniquely international approach to this complex environment, the result of an international team of authors and real-life cases from across the globe. This new edition has been fully revised with new and updated case studies from a variety of regions. Every chapter has been brought in line with current business-to-business research, alongside new coverage of non-profit and government marketing, digital marketing, ethics and corporate social responsibility. Other unique features include: the placement of B2B in a strategic marketing context; a full discussion of strategy in a global setting including hypercompetition; a detailed review of global B2B services marketing, trade shows and market research. More selective, shorter, and easier to read than other B2B textbooks, this is ideal for introductory B2B and intensive courses. It is also comprehensive enough to cover all the aspects of B2B marketing management that any marketer needs, whether they are students or practitioners seeking to improve their knowledge. The textbook is also accompanied by an extensive collection of resources to aid tutors, including a full set of PowerPoint slides, test bank of questions, and practical exercises to aid student learning"- Resumé vydavatel
Keywords: průmyslový marketing; marketingový management; industrial marketing; marketing management; učebnice vysokých škol; textbooks (higher)